2010
DOI: 10.1002/adma.200903712
|View full text |Cite
|
Sign up to set email alerts
|

Microstructural Characterization and Charge Transport in Thin Films of Conjugated Polymers

Abstract: The performance of semiconducting polymers has been steadily increasing in the last 20 years. Improved control over the microstructure of these materials and a deeper understanding of how the microstructure affects charge transport are partially responsible for such trend. The development and widespread use of techniques that allow to characterize the microstructure of semiconducting polymers is therefore instrumental for the advance of these materials. This article is a review of the characterization techniqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

16
513
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 477 publications
(533 citation statements)
references
References 222 publications
(291 reference statements)
16
513
0
Order By: Relevance
“…DISCUSSION Various groups have evidenced the importance of macromolecular parameters (regioregularity and molecular weight) of P3AT's on the formation of edge-on and face-on oriented crystallites and the correlations with the performances of solar cells and OFETs. 1,7,8,18,30 Regarding morphology of spin-coated P3HT films, nanofibrils are most often observed via AFM 4,16,17 Annealing is reported to favor the growth of long P3HT nanofibrils. 15,17 Cho et al reported a 2-fold increase of charge mobility upon annealing a P3HT (M w = 40 kDa) dip-coated film at 150°C for 15 min.…”
Section: Methodsmentioning
confidence: 99%
“…DISCUSSION Various groups have evidenced the importance of macromolecular parameters (regioregularity and molecular weight) of P3AT's on the formation of edge-on and face-on oriented crystallites and the correlations with the performances of solar cells and OFETs. 1,7,8,18,30 Regarding morphology of spin-coated P3HT films, nanofibrils are most often observed via AFM 4,16,17 Annealing is reported to favor the growth of long P3HT nanofibrils. 15,17 Cho et al reported a 2-fold increase of charge mobility upon annealing a P3HT (M w = 40 kDa) dip-coated film at 150°C for 15 min.…”
Section: Methodsmentioning
confidence: 99%
“…Elusive issues include the non-trivial influence of the multiple sources of disorder (for example, semi-crystallinity, paracrystallinity and nanoscale inhomogeneity [1][2][3][4][5][6][7], the elucidation of the important hopping mechanisms [1][2][3][4][7][8][9][10] , the effects of charge carrier-lattice interactions 3,4 and the identification of the ultimate limits on conductivity and mobility [1][2][3][4][5][6]11 . The latter is particularly important as, in addition to being of considerable fundamental interest the upper limits on conductivity and mobility also limit device performance (for example, transistor output current and operating frequency).…”
mentioning
confidence: 99%
“…In this way, the robustness, transparency and electronic properties of the inorganic materials are then combined with the possibilities offered by the organic lumophores giving rise to Hybrid Light Emitting Diodes (see Scheme 1). These devices, which have shown similar performances to those of the best published polymeric OLEDS, 18 are formed by sandwiching organic electroluminescent polymers between an electron transport layer (ETL) such as ZnO, TiO 2 or ZrO 2 and a MoO 3 hole transport layer (HTL) topped with an inert high work function gold anode. [19][20][21] In addition, the low cost and the facile preparation of the metal oxides permit the reduction of production costs and the fabrication of devices in air by solution methods.…”
Section: Introductionmentioning
confidence: 82%